Effects of marathon running on running economy and kinematics - Kyröläinen, H.; Pullinen, T.; Candau, R.; Avela, J.; Huttunen, P.; Komi, P. V. (European Journal of Applied Physiology, 2000)
The present study was designed to investigate interactions between running economy and mechanics before, during, and after an individually run marathon. Seven experienced triathletes performed a 5-min submaximal running test on a treadmill at an individual constant marathon speed. Heart rate was monitored and the expired respiratory gas was analyzed. Blood samples were drawn to analyze serum creatine kinase activity (S-CK), skeletal troponin I (sTnI), and blood lactate (B-La). A video analysis was performed (200 frames · s-1) to investigate running mechanics. A kinematic arm was used to determine the external work of each subject. The results of the present study demonstrate that after the marathon, a standardized 5-min submaximal running test resulted in an increase in oxygen consumption, ventilation, and heart rate (P < 0.05), with a simultaneous decrease in the oxygen difference (%) between inspired and expired air, and respiratory exchange ratio (P < 0.05). B-La did not change during the marathon, while sTnI and S-CK values increased (P < 0.05), peaking 2 h and 2 days after the marathon, respectively. With regard to the running kinematics, a minor increase in stride frequency and a similar decrease in stride length were observed (P < 0.01). These results demonstrate clearly that weakened running economy cannot be explained by changes in running mechanics. Therefore, it is suggested that the increased physiological loading is due to several mechanisms: increased utilization of fat as an energy substrate, increased demands of body temperature regulation, and possible muscle damage.